2017
DOI: 10.1111/jne.12446
|View full text |Cite
|
Sign up to set email alerts
|

Mild Thyrotoxicosis Leads to Brain Perfusion Changes: An Arterial Spin Labelling Study

Abstract: Hypo- and hyperthyroidism have effects on brain structure and function, as well as cognitive processes, including memory. However, little is known about the influence of thyroid hormones on brain perfusion and the relationship of such perfusion changes with cognition. The present study aimed to demonstrate the effect of short-term experimental hyperthyroidism on brain perfusion in healthy volunteers and to assess whether perfusion changes, if present, are related to cognitive performance. It is known that an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…The high expression of TRalpha characterised during cerebellar development is in line with our present finding of a particularly high vulnerability of cerebellar structures to small changes in thyroid function even in adults. This hypothesis also fits with our previous work in experimental hyperthyroidism where, amongst other regions, cerebellar activation is altered in a comparable memory task (Figure and Table ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The high expression of TRalpha characterised during cerebellar development is in line with our present finding of a particularly high vulnerability of cerebellar structures to small changes in thyroid function even in adults. This hypothesis also fits with our previous work in experimental hyperthyroidism where, amongst other regions, cerebellar activation is altered in a comparable memory task (Figure and Table ).…”
Section: Discussionsupporting
confidence: 92%
“…Previously, our group used structural and functional MRI, with the latter in conjunction with an n‐back task, to assess a model of experimentally induced hyperthyroidism . The fMRI study revealed an effect of task difficulty in the parahippocampal gyrus, supplementary motor area, prefrontal cortex, anterior cingulate cortex, posterior cerebellum, rolandic operculum and insula, with a modulation of this effect by thyroid status (hyperthyroid vs euthyroid) in the right prefrontal cortex and the right parahippocampal area.…”
Section: Introductionmentioning
confidence: 99%
“…Previous attempts to visualise and understand thyroid–brain interaction combined neuroimaging with neurophysiological and neuropsychiatric investigations 22 90. Cognition is complex and, as such, involves widely distributed functional systems and several brain regions, among which the MTL and the prefrontal cortex are generally recognised as being of central importance.…”
Section: Methods and Analysismentioning
confidence: 99%
“…The posterior cerebellum, among other regions, is probably relevant for cognition in GD. Experimentally induced hyperthyroidism increases brain perfusion in posterior cerebellar regions connected with cerebral networks thought to be associated with cognitive control 90. In the German version of the Auditory Verbal Learning scale, these perfusion changes are positively correlated with changes in performance 90.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Previous neuroimaging studies have shown morphological, functional, metabolite and perfusion weighted changes associated with thyrotoxicosis. A functional magnetic resonance imaging (fMRI) study using the N‐back working memory task revealed altered activation in brain regions such as the parahippocampal gyrus, supplementary motor area, prefrontal cortex, anterior cingulate cortex, posterior cerebellum, rolandic operculum and insula in thyrotoxicosis .…”
Section: Introductionmentioning
confidence: 99%